Intensive glycemic control and kidney disease risk: insights on hierarchical composite endpoint from a randomized clinical trial - Song, Zhaojie; Xu, Haibao; Zhang, Jiaheng; Liu, Yezhou; Li, Chao; Chen, Tao; Guo, Sujuan; Zhu, Ni (Frontiers in Medicine, 2025)
BackgroundClinical trials of intensive glycemic control in patients with type 2 diabetes mellitus (T2DM) and high cardiovascular risk have reported inconsistent findings regarding chronic kidney disease (CKD) outcomes, partly due to heterogeneity in event definitions and reliance on conventional time-to-first-event analysis. This study aimed to evaluate the renal effects of intensive glycemic control using a hierarchical composite endpoint (HCE) ranked by clinical severity and analyzed via the Win Odds (WO) method.MethodThis post-hoc analysis included patients from the Action to Control Cardiovascular Risk in Diabetes (ACCORD) glycemia trial. We employed the win ratio statistical method to estimate the treatment effects on HCE, defined as a ranked composite of all-cause mortality, kidney failure, sustained estimated glomerular filtration rate (eGFR) declines of 57, 50, and 40% from baseline, persistent eGFR < 15 mL/min/1.73 m2, and eGFR slope. The effects of intensive glycemic control on individual HCE components and various composite kidney endpoints was assessed by Cox regression models.ResultsAmong the 9,848 participants, sustained 40% eGFR decline was the most frequent renal event in the hierarchical composite. Intensive glucose control was not associated with a significant difference in the HCE compared to standard therapy (WO = 1.03, 95% CI: 0.99–1.07). This finding was consistent with results from Cox regression (HR = 1.05, 95% CI: 0.97–1.13) and across individual components of the composite endpoint.ConclusionIn individuals with T2DM at high risk for cardiovascular disease, intensive glycemic control does not demonstrate a significantly detrimental effect on hierarchical composite kidney outcomes.